Analisis Keanekaragaman Genetik dan Diferensiasi Jati Jawa dan Madura berdasarkan Marka Mikrosatelit untuk Mendukung Fingerprinting Jati - Endah Suwarni; Munisyatul Millah; Noor Aini Habibah (Biosaintifika: Journal of Biology & Biology Education, 2010)
Analysis fingerprinting teak is supported by information about teak’s character molecularly. The information is gotten by analyzing 3 primary microsatellite in 46 teak samples that produce total 18 kinds of alel averagely 6 alel per locus. Genetics variety level is shown by Observed Heterozigosity (Ho), Expected Heterozygosity (He), Polimorfi sm Information Content (PIC) and Genetics Differentiation Coeffi cient successively 0.5122; 0.6221; 0.5818; and 0.0629. Kinship connection through dendogram analysis produces coeffi cient resemblance 0.3-1.00 that form 2 groups. However it has not shown inclination of forming group based on origin grows yet. Genetics differentiation analysis indicates different genetics in a population is higher then it is between populations. Analysis result has not found specifi c alel yet but has found 12 specifi c genotipe that is potential for analyzing fi ngerprinting if it relates to important useful genes. Keywords: microsatellite teak, DNA fi ngerprinting